The extreme pressure and lubricating behaviors of potassium borate nanoparticles as additive in PAO. (17th November 2019) - Li, Yi; Zhang, Songwei; Ding, Qi; Tang, Jinzhu; Qin, Baofeng; Hu, Litian
ABSTRACT: The potassium borate nanoparticles (nPB) as lubricant additive were prepared with an eco-friendly method. The tribological properties of nPB and ZDDP as lubricant additives in polyalphaolefin (PAO) were systematically evaluated using a four-ball tribometer and a SRV fretting friction and wear tester, which suggested that nPB exhibited excellent extreme pressure capacity, and better anti-wear and friction-reducing properties than ZDDP. Results of surface analyses show that the good lubricating properties and excellent load-carrying capacity of nPB in PAO are ascribed to the boundary protecting films, which were composed of some easy-shearing compounds: B2 O3, Fex By and Fe2 O3 .